The Concept of ‘Knowledge’ in Islam and Other Religions - İzzetgil, Zamire and İzzetgil, Elşan (Scholarya Demo Journal of Ruby, 2022)
The concept of ‘knowledge’ is not a new phenomenon in the field of religious studies. It is defined and interpreted differently in every religion. In Islam, the concept of ‘knowledge’ is used as the word (علمْ) and is mentioned 854 times in the Holy Quran. It has several variants in the form of a noun, verb, and infinitive. Generally, (علمْ) knowledge stands for feeling, recognizing, understanding, and comprehending. In Judaism, there are two words such as ‘yada’ and ‘da’at,’ which have a common root in the Semitic languages. The meaning of ‘yada’ and ‘da’at’ varies depending on the context. It appears six times in Psalm. In Christianity, the word ‘knowledge’ is used in the Bible, and the meaning of the word is to understand, to recognize, or to acknowledge. Knowledge, according to the Bible, is a gift from its creator, God. The gift of knowledge refers to the ability to know facts or details about something that could not have been known by natural means. The study intends to show how Islam, Christianity, and Judaism define and interpret the meaning of the concept of ‘knowledge’ within the framework of the Quran, Bible, and Torah. It discusses the significance of this research in revealing how the concept of ‘knowledge’ is approached in the specified religions in terms of etymological, epistemological, methodological, and scope. This research will be examined under five sub-titles: the etymology of the study under the first title, the purpose under the second title, the source of the study under the third title, the epistemology under the fourth title, and the methodology under the last title.